Lichen transplants at our service for atmospheric NH3 deposition assessments - Branquinho, Cristina (2011)
Atmospheric ammonia (NH3) is increasingly a major worldwide driver for biodiversity loss. Because this pollutant undergoes rapid chemical inter-conversions and deposition, it can be challenging to monitor. Our aim was to develop a biomonitoring system to evaluate atmospheric deposition of NH3. To do this, we measured concentrations of several N-related variables in lichen transplants including intercellular, extracellular, and bound fractions of ammonium (NH4 +); total nitrogen; and carbon to nitrogen ratios. We found extracellular NH4 + to be the best indicator of atmospheric NH3 deposition in 15-day lichen transplants. For transplants exposed longer than 15 days, intercellular NH4 + was the best indicator of NH3 deposition. Equilibration is achieved quite rapidly: bound NH4 + equilibrated in less than 15 days and 35-day transplants accumulated 72 % of the extracellular NH4 + concentrations present in in-situ lichens. Changes in total N concentrations also occurred very rapidly; a twofold increase in N concentration was observed in 35-day lichen transplants. The lichen transplants proved to be good monitors of short-term spatial and temporal variations in atmospheric NH3. Lichen transplants can help to standardize biomonitoring procedures since they have the same background levels and can be exposed in the same conditions.